ANALISIS PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI SERTA IMPLIKASINYA TERHADAP PENGANGGURAN DAN KEMISKINAN - Rina Madyasari (JURNAL EKONOMI PERJUANGAN, 2021)
This research aims to see the direct influence of financial performance variable in the form of independence ratio, effectiveness ratio and efficiency ratio of economic growth, unemployment and poverty, to see the direct impact of economic growth on poverty unemployment, and to see the direct impact of unemployment on poverty. The method used was case study. Data in this research is secondary data including Realization Report of Revenue and Expenditure Budget (APBD), the rate of economic growth, the rate of unemployment and the rate of poverty in Tasikmalaya cities starting from 2008 until 2013. This research using statistics descriptif and path analysis of research variable. The result of the research showed that financial performance namely of independence ratio have positive significant effect on economic growth, while the effectiveness ratio and efficiency ratio have negative effect on economic growth. Independence ratio also have negative effect on unemployment and poverty, while the effectiveness ratio and efficiency ratio have positive effect on unemployment and poverty. Economic growth gives negative effect in unemployment, while gives positive effect on poverty. Unemployment gives significant effect on poverty. Keyword : financial performance, economic growth, poverty, unemployment